Preparation of Poly(ethylene terephthalate)-graft-polystyrene Copolymer - Li, Zhenquan; Xie, Jianjun; Zhang, Xinying (Asian Journal of Chemistry, 2014)
The graft copolymerization of proper polymer onto poly(ethylene terephthalate) (PET) and nylon 6 (PA6) was conducted in order to control the ester-amide exchange reaction between these two polymers. This paper focuses on the graft polymerization of poly(ethylene terephthalate) and polystyrene (PS). The PET-g-PS copolymer was prepared at the presence of the dicumylperoxide (DCP) by melt grafted copolymerization. The effects of the reactant ratios, initiator concentrations, reaction time and reaction temperature on the grafting efficiency were discussed. The results indicated that the grafting efficiency of polystyrene was higher at the following conditions: the dicumylperoxide concentration was 0.2 wt %, the ratio of PET/PS was 10:1, the reaction temperature was 270 ºC and the reaction time was 5 min. FTIR, 1H NMR were used to prove that polystyrene had been grafted on poly(ethylene terephthalate) chain.